2017
DOI: 10.1007/s11934-017-0739-y
|View full text |Cite
|
Sign up to set email alerts
|

New Devices and Technologies for the Management of Overactive Bladder

Abstract: Modifications to already established therapies such as sacral nerve stimulation (SNS) or tibial nerve stimulation (TNS) are currently being studied for refractory OAB. On the SNS front, a newly rechargeable, smaller neurostimulator has been developed and has shown promising results for the treatment of refractory OAB. There are two newly implantable TNS devices actively being studied for the treatment of refractory OAB. These implanted TNS systems will allow the patient to receive treatment from the comfort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The Bioness StimRouter is a custom-made lead transcutaneously powered by an external pulse generator (EPG). A receiver, electrodes, and an anchoring system are all included in the implanted lead [ 60 ]. During implantation, ultrasound or fluoroscopic imaging may aid with the stimulation probes' placement, which is used to test stimulation to ensure proper peripheral nerve targeting.…”
Section: Posterior Tibial Nerve Stimulation Classificationsmentioning
confidence: 99%
“…The Bioness StimRouter is a custom-made lead transcutaneously powered by an external pulse generator (EPG). A receiver, electrodes, and an anchoring system are all included in the implanted lead [ 60 ]. During implantation, ultrasound or fluoroscopic imaging may aid with the stimulation probes' placement, which is used to test stimulation to ensure proper peripheral nerve targeting.…”
Section: Posterior Tibial Nerve Stimulation Classificationsmentioning
confidence: 99%
“…Studies have shown that within a year, between 30% and 70% of patients with OAB discontinue pharmacotherapy [82,83]. Hence, various stimulation devices are an alternative next-in-line treatment option for OAB and although they are more invasive, they have shown better improvement for OAB [53].…”
Section: Nerve Stimulation Devicesmentioning
confidence: 99%
“…Clinically approved and research-based electronic device solutions for overactive bladder (OAB), underactive bladder (UAB) and other-urinary-affecting disorders (OUAD). Clinically approved electronic solutions include InterStim [40], Axonics modulation technologies [53], inFlow [39], robotic surgery [54,55], ultrasonography systems [56,57] and near-infrared spectroscopy [58].…”
Section: Introductionmentioning
confidence: 99%
“…SNS is performed with a stimulator and electrodes implanted on sacral nerves 2-4 which provide continuous stimulation to the nerve. SNS implants were initially introduced to the market by Medtronic as InterStim, and since then, Axonics Modulation Technologies Inc (Irvine, CA, USA) have developed smaller and rechargeable implants [136]. SNS has been trialed in a number of studies to improve symptoms and quality of life in constipation, but the evidence that SNS is effective for constipation is limited [137,138].…”
Section: Therapiesmentioning
confidence: 99%